Taxonomic review of dwarf species of Eumicrotremus (Actinopterygii: Cottoidei: Cyclopteridae) with descriptions of two new species from the western North Pacific - Lee, Soo Jeong; Kim, Jin-Koo; Kai, Yoshiaki; Ikeguchi, Shin’ichiro; Nakabo, Tetsuji (Zootaxa, 2017)
A taxonomic review of the dwarf species of the genus Eumicrotremus (Actinopterygii: Cottoidei: Cyclopteridae), previously recognized as belonging to Lethotremus, established the existence of three species, viz. Eumicrotremus awae (Jordan and Snyder, 1902), Eumicrotremus uenoi sp. nov., and Eumicrotremus jindoensis sp. nov., from the western North Pacific. Eumicrotremus awae, known from the Pacific coast of Honshu Is. (Chiba southward to Mie), is characterized by the absence of spiny tubercles or fleshy papillae on the body, the anterior three mandibular pores each with a barbel-like tube, interorbital and suborbital pores usually absent, the opercular flap rounded, many papillae present on the ventral disk and the caudal-fin relatively short, 21.0–30.5% of SL (standard length). Eumicrotremus uenoi, known from the western coast of Honshu Is. and the southern coast of Korean Peninsula, is characterized by the absence of spiny tubercles or fleshy papillae on the body (or weak if present), the anterior three mandibular pores each with a barbel-like tube, interorbital and suborbital pores usually present, the opercular flap rounded, the ventral disk with many papillae and the caudal-fin relatively short, 19.5–31.4% of SL. Eumicrotremus jindoensis, known from the southwestern coast of Korean Peninsula, and the coasts of Yellow Sea, is characterized by a smooth soft body, triangular opercular flap, absence of papillae on the ventral disk and a long caudal fin, 32.7–42.1% of SL. Sequence variations of the mictochondrial DNA cytochrome c oxidase subunit I (mtDNA COI) and the nuclear myh6 genes supported the validity of the three species.